Mechanical model and contact properties of double row slewing ball bearing for wind turbine - Zhang Hongwei (De Gruyter, 2021)
In this paper, the mechanical models of large-scale double row slewing ball bearing considering combined loading conditions were presented based on the rigid rings and flexible rings, respectively. And the contact properties between the ball and raceway were studied. These workflows for the calculation were described and programmed by MATLAB. The load distributions of slewing bearing for 2MW wind turbine were presented. The results indicated that the load distribution with the ideal stiff assumption differs from the load distribution determined by taking into account the flexibility of rings. With flexible rings, the magnitude of contact force is less than that of the rigid rings. The influences of the initial contact angle, the coefficient of groove curvature radius, the clearance on maximum contact force were analyzed and some suggestions have been discussed. These parameters have significant effects on the load distribution. The maximum contact force decreases with coefficient of groove curvature radius decrease. A three dimensional finite element model of the slewing bearing is established and analyzed. The simulated results are compared with that of mechanical models.